Experimental Investigation of AA6063 Welded Joints Using FSW. (19th September 2022) - Rajkumar, T.; Radhakrishnan, K.; Rajaganapathy, C.; Jani, S. P.; Ummal Salmaan, Nowshadth
Abstract : The AA6063 aluminium alloy has gained widespread use in manufacturing the light-weighted structures which requires a high strength to weight ratio, and it possesses an excellent corrosive resistance in T6 heat-treated (solution heat treated and artificially aged) condition. The process of friction stir welding (FSW) is an emerging joining process of solid state that does not melt and recast the material being welded, as opposed in various other fusion welding processes, which are extensively utilized for combining the structural alloys of aluminium. The process of connecting separate components with external heat has resulted in induced stress on metals. The stir welding using friction was introduced in order to reduce the formation in residual stress during the joining process. The aluminium alloy AA6063 plates were fused utilising the friction stir welding procedure in this study. The studies were carried out using various combinations of speed in rotary condition, speed in transverse condition, and stress in axial condition. The generated joints that are welded was analysed mechanically and microstructurally. The maximum hardness of the mechanical joints produced is 93.25 HV, and the maximum tensile strength is 286.15 N/mm 2 . According to the results of the response surface analysis, transverse and rotary velocities possess a notable impact in hardness and durability, respectively.